Whose testimony is believed? linguistic credibility, gendered narratives, and institutional power in Indonesian sexual violence judgments - Ghania Maham (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Sexual violence adjudication in Indonesia increasingly depends not only on legal proof, but also on how courts linguistically construct whose testimony becomes believable, doubtful, admissible, or insufficient. Objective: This study examines how linguistic credibility, gendered narrative positioning, and institutional power are textualised in Indonesian sexual violence judgments. Method: Using a qualitative legal discourse design, this study analyses 11 judgment-related text units drawn from a public corpus of court judgments and judgment-linked legal documents, combining forensic linguistic analysis, feminist legal theory, and critical discourse analysis. Results: The findings show that credibility is produced through judicial revoicing, evidentiary sequencing, corroborative uptake, procedural framing, and legal thresholding. Victim testimony is often made persuasive when attached to recognised signs of vulnerability, medical or psychological corroboration, object evidence, or institutional validation, while disbelief is expressed through explicit judicial formulations of doubt and insufficiency. Implication: Institutional power operates by ranking victim testimony, defendant denial, witness statements, expert reports, documentary proof, and statutory elements within a hierarchy of legal intelligibility. Novelty: This study contributes a discourse-based account of testimonial belief in Indonesian sexual violence adjudication by shifting attention from whether testimony is accepted to how credibility is linguistically and institutionally made possible.